Wilder than intense: higher frequency, variability, and viral flows of porcine circovirus 3 in wild boars and rural farms compared to intensive ones in northern Italy - Franzo, Giovanni; Faustini, Giulia; Legnardi, Matteo; Berto, Giacomo; Dal Maso, Mariangela; Genna, Viviana; Menandro, Maria Luisa; Poletto, Francesca; Cecchinato, Mattia; Drigo, Michele; Tucciarone, Claudia Maria (Frontiers in Microbiology, 2023)
Porcine circovirus 3 (PCV-3) is a recently discovered circovirus of swinewas firstly reported in 2017.Although evidence of its pathogenic role has been provided, its clinical relevance seems lower than the Porcine circovirus 2 (PCV-2), as well as its evolutionary rate. Different studies have reported a high PCV-3 prevalence in wild boars, sometimes higher than the one observed in commercial pigs.Nevertheless, to date, few studies have objectively investigated the relationships between these populations when inhabiting the same area. Moreover, the role of small-scale, backyard pig production in PCV-3 epidemiology is still obscure. The present study investigated PCV-3 occurrence in 216 samples collected from the same area of Northern Italy from commercial and rural pigs, and wild boars. PCV-3 presence was tested by qPCR and complete genome or ORF2 sequences were obtained when possible. A combination of statistical, phylogenetic and phylodynamic approaches highlighted a higher infection risk in wild boars and rural pigs compared to the commercial ones. The phylodynamic analysis confirmed a larger viral population size in wild and rural populations and estimated a preferential viral flow from these populations to commercial pigs. A significant flow from wild to rural animals was also proven. The analysis of the Italian sequences and the comparison with a broader international reference dataset highlighted the circulation of a highly divergent clade in Italian rural pigs and wild boars only. Overall, the present study results demonstrate the role of non-commercial pig populations in PCV-3 maintenance, epidemiology and evolution, which could represent a threat to intensive farming.